Surveillance of tuberculosis incidence and mortality through spatio-temporal analysis in Oyo State, Nigeria - Teibo, Titilade Kehinde Ayandeyi; Berra, Thais Zamboni; Alves, Yan Mathias; Tavares, Reginaldo Bazon Vaz; Olayemi, Oluwaseyi Ademo; Arcêncio, Ricardo Alexandre (PloS one, 2025)
The study aimed to describe the epidemiological profile of Tuberculosis (TB) and analyze the spatial distribution and temporal trend of TB incidence and mortality in Oyo state Nigeria from 2015–2019. The study was composed of TB cases and deaths reported by the Oyo State Health Secretariat between 2015 and 2019. The purely spatial, space-time scanning and the Getis-Ord Gi* techniques were used to analyze the spatial characteristics of TB and to identify areas at risk for its occurrence and deaths based on rates in each unit of analysis - Local Government Area (LGA), while the time series analysis technique was used to assess the characteristics of TB in Oyo state over the period studied. The standardized rates of sex and age were considered for data analysis. We analyzed 28,670 new cases of pulmonary and extra pulmonary TB as well as 1142 deaths reported in all LGAs between 2015 and 2019. Ibadan South West local government had the highest rate and risk (334 cases per 100,000), solely constituting above 10% of all cases reported in all 33 LGAs and for deaths the rate was 19.01 cases/100,000 inhabitants. Ido and Oluyole LGAs were Hot Spot regions for TB with a 99% confidence interval (CI) for TB incidence; about TB mortality, five municipalities were identified with a spatial association at 95% CI. The historical series of TB incidence rate slightly increased between the years 2015–2017, with a sharp decline from then until 2019. The temporal trend for the incidence and mortality of TB in the period under study decreased. This study contributes to knowing the epidemiological profile, the spatial and temporal distribution, and areas with higher risk of TB transmission in Oyo state. This makes it possible for policy makers to target hotspot areas for intervention and disease prevention.